Asia's next giant : - Amsden, Alice H. (Oxford University Press, 1989)
South Korea has been quietly growing into a major economic force that is even challenging some Japanese industries. This timely book examines South Korean growth as an example of "late industrialization," a process in which a nation's industries learn from earlier innovator nations, rather than innovate themselves. Discussing state intervention, shop floor management, and big business groups, Amsden explores the reasons for South Korea's phenomenal growth, paying special attention to the principle of reciprocity in which the government imposes strict performance standards on those industries and companies that it aids. She thereby shows how South Korea, Japan, and Taiwan were able to grow faster than other emerging nations such as Brazil, Turkey, India, and Mexico.